2023
DOI: 10.1039/d3cc01940c
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(iii)-catalyzed mild and regioselective dearomative spirocyclization of 2-aryl-3-nitrosoindoles with alkynes

Abstract: Herein, we develop a Rh(III)-catalyzed intermolecular regioselective dearomative spirocyclization of 2-aryl-3-nitrosoindoles with alkynes, featuring the redox-neutral and atom-economy construction of spiroindoline-3-one oximes bearing a C2 spirocyclic quaternary carbon center under...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…When 18 O‐labeled water was added to the model reaction, indenones containing 18 O‐ and 16 O‐atom were afforded in high yield, which indicated that the hydrolysis is involved in the formation of indenone (Scheme 2e). The isotope labeling experiments and detection of by‐product 2‐aminobenzonitrile implied hydrolysis of an imine cation, that was most likely generated from spirocyclicindoline 3 aa‐oxime via N−O and C−C bond cleavage according to our previous works (Scheme 2f) [19,20] …”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…When 18 O‐labeled water was added to the model reaction, indenones containing 18 O‐ and 16 O‐atom were afforded in high yield, which indicated that the hydrolysis is involved in the formation of indenone (Scheme 2e). The isotope labeling experiments and detection of by‐product 2‐aminobenzonitrile implied hydrolysis of an imine cation, that was most likely generated from spirocyclicindoline 3 aa‐oxime via N−O and C−C bond cleavage according to our previous works (Scheme 2f) [19,20] …”
Section: Methodsmentioning
confidence: 85%
“…The isotope labeling experiments and detection of by-product 2-aminobenzonitrile implied hydrolysis of an imine cation, that was most likely generated from spirocyclicindoline 3 aa-oxime via NÀ O and CÀ C bond cleavage according to our previous works (Scheme 2f). [19,20] To obtain the detailed pathway on the formation of the above-mentioned spirocyclic intermediate, the density functional theory (DFT) calculation was performed. The reaction of indole 1 a with alkyne 2 a at 363.15 K was discussed (Figure 1).…”
Section: Updates Ascwiley-vchdementioning
confidence: 99%
See 1 more Smart Citation
“…The 1,3-diynes also took part in the reaction to afford alkyne-containing C2-spiroindolines (Scheme 11). 11…”
Section: Cha-initiated Spiroannulation With Alkynes As the Coupling P...mentioning
confidence: 99%